The liability of public authorities in comparative perspective / edited by Ken Oliphant. - Oliphant, Ken (Principles of European tort law (European Group on Tort Law), 2016)
In recent decades, the liability of public authorities has been one of the main areas of development in and at the edges of tort law in Europe, with major reforms implemented or considered at a national level, and a steady stream of major court decisions. During the same period, 'Member State liability' has also been recognised in the law of the EU, and the interplay of principles of national and EU law - and additionally the 'just satisfaction' jurisprudence of the European Court of Human Rights - evidently warrants close attention.In this context, the aims of the present study are to contribute to the understanding of the law of extra-contractual liability as it applies to public authorities in the legal systems of Europe (and selected non-European jurisdictions), to facilitate its enhancement where necessary or desirable, and to consider the possibilities for harmonisation in the area - specifically, through the extension and adaptation of the Principles of European Tort Law to cover public authority liability.